Towards a Holistic Sustainability Evaluation for Transport Alternatives - Nguyen, Thu Trang; Brunner, Helmut; Hirz, Mario (European Journal of Sustainable Development, 2020)
The transport sector is responsible for a broad range of ecologic impacts, e.g., energy consumption, greenhouse gas emission or air pollution. It is therefore highly important to assess transport solutions in terms of their sustainability. Widely used approaches for sustainability analysis in the transport sector include life cycle assessment (LCA), economic approach, multi-criteria decision analysis (MDCA), and assessments based on indicators. In practice, these approaches consist of several methods, i.e., product-based LCA, fleet-based LCA, cost benefit analysis (CBA), cost effectiveness analysis (CEA), value measurement MDCA, ideal-solution based MDCA, outranking MDCA, and indicator-based assessment. Even though there is a larger number of assessment methods, a holistic framework for sustainability evaluation of different transport solutions is still missing. Selection of suitable assessment methods depends on a vast array of factors. This paper proposes to utilise “application levels” for the selection process. Firstly, the paper provides an analysis of the application levels of the common assessment methods and evaluation criteria within the transport sector based on a literature review. The application levels are illustrated by identifying two dimensions, namely system level and decision-making level, ranging from Low to High. Afterwards, a six-step framework for a holistic evaluation of transport alternatives is proposed. Keywords: sustainability assessment, economic approach, indicator-based assessment, life cycle assessment, multi-criteria decision analysis, sustainable transport